Strategi Dinas Lingkungan Hidup dan Kebersihan Dalam Menanggulangi Tumpukan Sampah di Tembilahan Kota - Pivit Septiary Chandra; Melysa (Al-Manar Journal of Public Administration and Management, 2025)
The environmental strategy to address the waste pile-up in Tembilahan City requires an integrated approach involving various parties. This study uses a qualitative research method with data collection techniques such as interviews, observation, and documentation. The research informants were selected using purposive sampling. This study employs triangulation techniques in data analysis. The theory applied in this research is the SWOT analysis theory by Freddy Rangkuti. The study highlights the importance of improving infrastructure, such as adding waste collection vehicles and waste processing facilities, as well as strengthening waste management policies that are more assertive and sustainable. In addition, the role of public education in raising awareness to sort and manage waste independently is a key element in this strategy. The research results show that the Environmental and Sanitation Office's strategy in addressing the waste pile-up in Tembilahan City has been well-implemented, but there are factors that influence the strategy. Internal factors such as limited resources and office management, as well as external factors such as the lack of public behavioral awareness, also affect the success of these efforts. Through collaboration between the government, private sector, and the community, waste management in Tembilahan City is expected to become more effective and sustainable, thus supporting the creation of a clean and healthy environment for the community.